Theory and practice of natural computing : 5th international conference, TPNC 2016, Sendai, Japan, December 12-13, 2016, proceedings /: 5th international conference, TPNC 2016, Sendai, Japan, December 12-13, 2016, proceedings. (2016) - Unknown
No abstract available